Triple‐Phase Computed Tomography May Replace Dual‐Energy X‐ray Absorptiometry Scan for Evaluation of Osteoporosis in Liver Transplant Candidates. Issue 3 (4th March 2021) - Izzy, Manhal; Addissie, Benyam D.; Arab, Juan Pablo; Hilscher, Moira B.; Cartee, Amanda; Lee, David C.; Lee, Yong; Fletcher, Joel G.; Keaveny, Tony M.; Sanchez, William
Abstract : Assessment of bone density is an important part of liver transplantation (LT) evaluation for early identification and treatment of osteoporosis. Dual‐energy X‐ray absorptiometry (DXA) is currently the standard clinical test for osteoporosis; however, it may contribute to the appointment burden on LT candidates during the cumbersome evaluation process, and there are limitations affecting its accuracy. In this study, we evaluate the utility of biomechanical analysis of vertebral images obtained during dual‐energy abdominal triple‐phase computed tomography (TPCT) in diagnosing osteoporosis among LT candidates. We retrospectively reviewed cases evaluated for LT between January 2017 and March 2018. All patients who underwent TPCT within 3 months of DXA were included. The biomechanical computed tomography (BCT) analysis was performed at a centralized laboratory (O.N. Diagnostics, Berkeley, CA) by 2 trained analysts blinded to the DXA data. DXA‐based osteoporosis was defined as a T score ≤−2.5 at the hip or spine. BCT‐based osteoporosis was defined as vertebral strength ≤4500 N for women or ≤6500 N for men or trabecular volumetric bone mineral density ≤80 mg/cm 3 . Comparative data were available for 91 patients who had complete data for both DXA and BCT: 31 women and 60 men, age 54 ± 11 years (mean ± standard deviation), mean body mass index 28 ± 6 kg/m 2 . Using DXA as the clinical reference, sensitivity of BCT to detect DXA‐defined osteoporosis was 83.3% (20/24 patients) and negative predictive value was 91.7%; specificity and positive predictive value were 65.7% and 46.5%, respectively. BCT analysis of vertebral images on triple‐phase computed tomography, routinely obtained during transplant evaluation, can reliably rule out osteoporosis in LT candidates. Patients with suspicion of osteoporosis on TPCT may need further evaluation by DXA.